The Influence of Charismatic Leadership Style, Job Training, And Work Self Efficacy on Job Satisfaction at PT. Wijaya Stelindo: Human Resource Management - Nur Cholis Majid; Retno Purwani Setyaningrum (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
This study discusses whether charismatic leadership style, job training, and job self-efficacy affect job satisfaction at PT. Wijaya Steelindo. The purpose of this study was to examine the effect of charismatic leadership style, job training and job self-efficacy on job satisfaction at PT. Wijaya Steelindo. This testing procedure utilizes non-likelihood examining and acquired upwards of 144 individuals who are workers of PT. Wijaya Steelindo. The information acquired were dissected quantitatively involving logical devices as legitimacy test tables, unwavering quality tests, old style suspicion tests, different relapse investigation, speculation testing, t tests, f tests, and coefficients of assurance involving the SPSS 25 for Windows application program. The consequences of the examination halfway insights show that magnetic initiative style and work self-viability significantly affect work fulfillment, while work preparing affects work fulfillment. Based on the huge worth of the alluring authority style T test (X1) of 0.000 and work preparing (X) of 0.779 while work self-adequacy (X3) is 0.015. The F test results are 0.000 with a R Square worth of 0.114 or 11.4% so the effect of appealling authority style, work planning, work self-sufficiency is 11.4% while 88.6% is impacted by various variables that are not examined in this survey.